New Insights on Gordonia alkanivorans Strain 1B Surface-Active Biomolecules: Gordofactin Properties - João Tavares; Susana M. Paixão; Tiago P. Silva; Luís Alves (Molecules)
Biosurfactants/bioemulsifiers (BSs/BEs) can be defined as surface-active biomolecules produced by microorganisms with a broad range of applications. In recent years, due to their unique properties like biodegradability, specificity, low toxicity, and relative ease of preparation, these biomolecules have attracted wide interest as an eco-friendly alternative for several industrial sectors, escalating global microbial BS/BE market growth. Recently, Gordonia alkanivorans strain 1B, a bacterium with significant biotechnological potential, well known for its biodesulfurizing properties, carotenoid production, and broad catabolic range, was described as a BS/BE producer. This study focuses on the characterization of the properties of the lipoglycopeptide BSs/BEs produced by strain 1B, henceforth referred to as gordofactin, to better understand its potential and future applications. Strain 1B was cultivated in a chemostat using fructose as a carbon source to stimulate gordofactin production, and different purification methods were tested. The most purified sample, designated as extracted gordofactin, after lyophilization, presented a specific emulsifying activity of 9.5 U/mg and a critical micelle concentration of 13.5 mg/L. FT-IR analysis revealed the presence of basic hydroxyl, carboxyl, ether, amine/amide functional groups, and alkyl aliphatic chains, which is consistent with its lipoglycopeptide nature (60% lipids, 19.6% carbohydrates, and 9% proteins). Gordofactin displayed remarkable stability and retained emulsifying activity across a broad range of temperatures (30 °C to 80 °C) and pH (pH 3–12). Moreover, a significant tolerance of gordofactin emulsifying activity (EA) to a wide range of NaCl concentrations (1 to 100 g/L) was demonstrated. Although with a great loss of EA in the presence of NaCl concentrations above 2.5%, gordofactin could still tolerate up to 100 g/L NaCl, maintaining about 16% of its initial EA for up to 7 days. Furthermore, gordofactin exhibited growth inhibition against both Gram-positive and Gram-negative bacteria, and it demonstrated concentration-dependent free radical scavenging activity for 2,2-diphenyl-1-picrylhydrazyl (IC50 ≈ 1471 mg/L). These promising features emphasize the robustness and potential of gordofactin as an eco-friendly BS/BE alternative to conventional surfactants/emulsifiers for different industrial applications.